2021
DOI: 10.1186/s12905-020-01165-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential risk of contralateral non-sentinel groin node metastasis in women with early primary vulvar cancer following unilateral sentinel node metastasis: a single center evaluation in University Hospital of Düsseldorf

Abstract: Background Since the introduction of sentinel node biopsy (SLNB) in unifocal vulvar cancer (diameter of < 4 cm) and unsuspicious groin lymph nodes, the morbidity rate of patients has significantly decreased globally. In contrast to SLNB, bilateral inguinofemoral lymphadenectomy (IFL) has been associated with increased risk of common morbidities. Current guidelines (NCCN, ESGO, RCOG, and German) recommend that in cases of unilaterally positive sentinel lymph node (SLN), bilateral IFL should b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Two retrospective monocentric studies suggested not treating contralateral groin, since they found very low rates of contralateral involvement: 0% (0/28) patients and 5.3% (1/19) patients, respectively [29,30]. However, a recent study reported a higher rate of contralateral involvement, at 22.2% (4/18) of patients, after an initial diagnosis of unilateral metastasis, supporting current guidelines in favor of contralateral prophylactic treatment by either lymphadenectomy or radiotherapy [31].…”
Section: Slnb Is a Well-documented Technique In Vulvar Cancersmentioning
confidence: 91%
“…Two retrospective monocentric studies suggested not treating contralateral groin, since they found very low rates of contralateral involvement: 0% (0/28) patients and 5.3% (1/19) patients, respectively [29,30]. However, a recent study reported a higher rate of contralateral involvement, at 22.2% (4/18) of patients, after an initial diagnosis of unilateral metastasis, supporting current guidelines in favor of contralateral prophylactic treatment by either lymphadenectomy or radiotherapy [31].…”
Section: Slnb Is a Well-documented Technique In Vulvar Cancersmentioning
confidence: 91%
“…[86][87][88] In contrast, data from a single institution identified contralateral positivity in 22% (4/18). 89 A more recent larger (n=244), prospective study from the GROINSS-V trial group provides evidence to support the omission of further treatment to the unaffected groin, providing bilateral drainage has been identified for true midline tumors. The authors found the incidence of a non-sentinel, contralateral metastasis to be 2.9% (7/244; 95% CI 1.4% to 5.8%), comparable to the risk of groin recurrence after a negative SNL dissection.…”
Section: Original Researchmentioning
confidence: 96%
“…[ 5 , 6 ] However many scholars challenge this paradigm and believe that ALND for patients with positive SLNs may be an excessive treatment, since 40% to 70% of breast cancer patients with SLN metastasis do not have non-sentinel lymph node (NSLN) metastasis. [ 7 9 ] The purpose of our study was to analyze the risk factors associated with NSLN metastasis in SLN-positive breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%